Paleoecological significance of Late Quaternary molluscan faunas of the Bahia San Blas area, Argentina - Charo, Melisa Paola (2013)
Late Quaternary marine deposits in the area of Bahía San Blas (Buenos Aires, Argentina) form beach ridges and tidal plains bearing remains of organisms, mainly mollusc shells. These mollusc assemblages were characterized, and their changes assessed both over time, and related to local environmental factors. Twenty-six sites were analyzed, eleven Pleistocene, seven Holocene and eight modern sites. Fifty taxa (27 bivalves and 23 gastropods) were recorded for the area, with marine species predominant over estuarine. Within gastropods, epifaunal species and carnivores are predominant, with a lower proportion of herbivores and filter feeders, while bivalves are mostly infaunal and suspension feeders. Pleistocene associations are characterized by the high quantity of molluscs in rocky environments, and those of the Holocene by the presence of the warm water Crassostrea rhizophorae, which is currently displaced to lower latitudes. Within the modern associations four taxa, Mesodesma mactroides, Solen tehuelchus, Barnea lamellosa and Crassostrea gigas (an introduced species), are not recorded as fossils, but Mesodesma mactroides is found in Holocene shell middens from the area. According to multivariate analysis, the sites were divided into two groups: high energy deposits (storm ridges) and low-energy deposits (tidal plains), regardless of their age. Based on these results, mollusc variations in the area are thought to be related in part to changes in temperature that took place since the Pleistocene (e.g. C. rhizophorae); but mostly associated with the presence of sub-environments of different energy levels. This would favor the presence of different taxa in accordance to their ecological requirements.